PENGARUH TINGKAT LITERASI MAHASISWA PERBANKAN SYARIAH TERHADAP INKLUSI KEUANGAN PRODUK PERBANKAN SYARIAH DALAM TRANSAKSI E_COMMERCE - Nur Melinda Lestari (Ekonomi Islam, 2019)
Survey of the Financial Services Authority (OJK) in early 2018 showed sharia financial literacy levels were only 8% based on inclusion rates, for sharia banks themselves reaching highest literacy rates of 6,6% literacy rates and 9% inclusion rates, this was the goal of the banking sharia, of the many obtained in each academic year, must be able to contribute to development of shariah banking literacy levels. Student markets are large for e-commerce and the market. This study looks at the level of financial inclusion of Islamic banking in e-commerce transactions. The instrument test was conducted to test the quality of the instruments used in the study using the classic assumption test, normality test, autocorrelation test, and heteroscedasticity test, the data analysis technique of this study used simple regression analysis. Keywords: Student Literacy Mahasiswa, M-banking Inclusion